Paradigm Of Student Development In Islamic Education: A Study Of Nativism, Empiricism, Convergence, and The Concept Of Fitrah - Zahra Lutvia Assagaf; Syarifuddin Ondeng; Muhammad Yahdi (CV PUTRA PUBLISHER, 2025)
Students are a central wede168 element in Islamic education, which is aimed at the comprehensive development of the whole person. In educational studies, student development is understood through various paradigms, including nativism, which emphasises innate factors; empiricism, which emphasises the influence of the environment and experience; and convergence, which combines these two factors. On the other hand, Islamic education has a unique concept of human nature, namely fitrah as a sacred basic potential bestowed by Allah SWT since birth. This article aims to examine the paradigm of student development based on the perspectives of nativism, empiricism, and convergence, as well as to analyse its relevance to the concept of fitrah in Islamic education. This study uses a qualitative approach through library research by analysing relevant books, journal articles, and scientific sources. The results show that each paradigm makes an important contribution to understanding student development, but has limitations when viewed in isolation. The concept of fitrah in Islamic education complements these three paradigms by emphasising that student development is the result of the interaction between innate potential, environment, and guidance from divine values. These findings confirm that Islamic education should ideally integrate all these aspects in a balanced manner so that the development of students' fitrah can take place optimally, in intellectual, moral, and spiritual dimensions.